Possible association of Typhoon Hagibis and the COVID‐19 pandemic on patient delay in breast cancer patients: A case report. Issue 3 (22nd March 2022) - Kaneda, Yudai; Ozaki, Akihiko; Wada, Masahiro; Kurokawa, Tomohiro; Sawano, Toyoaki; Tsubokura, Masaharu; Tanimoto, Tetsuya; Kanemoto, Yoshiaki; Ejiri, Tomozo; Kanzaki, Norio
Abstract: Little is known on how different types of disasters interact in their impacts on patient care. We experienced a breast cancer patient whose initial presentation was delayed for 2 years due to the COVID‐19 pandemic and Typhoon Hagibis. Increasing awareness is needed on the combined impacts of disasters on breast cancer management. Abstract : Timely presentation is critical in breast and other cancer management, but disasters may hamper these processes. Particularly, disaster impacts on cancer care can be intensified when combined, which should be noted during the COVID‐19 pandemic.